2018
DOI: 10.3390/molecules23123207
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of South African Herbal Tisanes, Rooibos and Honeybush in the Management of Type 2 Diabetes Mellitus

Abstract: Diabetes mellitus is a metabolic disease that can lead to high morbidity, mortality and long-term complications. Available treatment strategies, which are mainly based on treating hyperglycemia, with insulin and other pharmacological agents are not completely efficient and can even lead to development of unwanted side effects. Scientific evidence suggests that bioactive compounds from teas and other plant-based foods, which are known source of natural antioxidants, could be an attractive strategy to preferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 131 publications
(150 reference statements)
1
38
0
Order By: Relevance
“…Thus, persuades us to suggest that the ethyl acetate and aqueous extracts of honeybush tea can be exploited as potent candidates for isolation of α‐glucosidase inhibitors which might be effective as therapeutic agents against T2D. The results in the present study further corroborates previous reports on the ability of honeybush teas to inhibit α‐glucosidase activities in vitro (Ajuwon, Ayeleso, & Adefolaju, 2018; Miller, Malherbe, & Joubert, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, persuades us to suggest that the ethyl acetate and aqueous extracts of honeybush tea can be exploited as potent candidates for isolation of α‐glucosidase inhibitors which might be effective as therapeutic agents against T2D. The results in the present study further corroborates previous reports on the ability of honeybush teas to inhibit α‐glucosidase activities in vitro (Ajuwon, Ayeleso, & Adefolaju, 2018; Miller, Malherbe, & Joubert, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…While the extracts from mango ( Mangifera indica L.) fruit peel [ 6 ], seeds, leaves [ 2 , 7 , 8 ], bark and roots [ 2 , 7 ] have been shown to contain this compound, MGF is also found abundantly in other plant species such as Salacia chinensis , Swertia chirata , Hypericum aucheri and Cyclopia intermedia [ 6 , 9 , 10 ]. The xanthones (MGF and isomangiferin) and flavanones (hesperitin and hesperidin) are the major components of C. intermedia extracts, and are thought to be responsible for most of its pharmacological effects, including anti-diabetic, anti-cancer, anti-obesity, antioxidant and antimicrobial activities [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of HB are commonly used to make herbal tea, which has many health benefits. HB is rich in antioxidants and the health benefits include the treatment of infections, coughs, sore throat, colds, osteoporosis, prevention of cancer and asthma [ 11 ]. The genus Cyclopia consists of some 20 species of flowering plants in the legume family, Fabaceae [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that HB extracts contain polyphenolic compounds which are correlated with the plant’s biological activities. The significant compounds, characterized and isolated from HB, are the xanthones (MGF and isomangiferin) and flavanones (hesperidin, and isosakuranetin) [ 78 , 79 ]. These polyphenols offer the HB plant the ability to improve the immune system, protect against inflammatory diseases, and inhibit antimicrobial and tumour growth [ 110 , 111 ].…”
Section: Biological Application Of Mnps Synthesized From Some Selected South African Medicinal Plantsmentioning
confidence: 99%